A Communication Strategy of Support Providers in Providing Supports For Sexual Violence Victims - Dwihadiah, Desideria Lumongga; Stephanie, Alya Hadijah (UI Scholars Hub, 2022)
Sexual violence is a big problem in society, because the negative impact on the victim causes prolonged suffering. Assistance for victims is carried out at the individual, group and institutional levels, both formal and informal. They act as support providers for sexual violence victims. Support providers often experience difficulties because victims find it difficult to open up due to the trauma they have experienced. A strategy to communicate is necessary, so the providers can well provide supports and assistances to victims. This study wanted to explore communication strategies used by support providers in dealing with and helping sexual violence victims. This study used a qualitative approach with descriptive analysis method. Data were collected through in-depth interviews. Informants from this study were support providers that deal with sexual violence victims. The key informants consisted of three people, namely a police officer for the women and children protection (PPA), psychologist who was a victim of sexual violence, and clergyman (church worker). The study results indicated that the support providers implemented a communication strategy by applying the principles of empathy, support and equality, so the victims were willing to open up and get help. They applied rapport techniques in building relationships, practiced active listening skills, and did self-disclosure to be on par with the victim, so the victims can be more open. Kekerasan seksual adalah masalah besar di masyarakat, karena dampak negatif pada korban menyebabkan penderitaan yang berkepanjangan. Pendampingan bagi korban dilakukan di tingkat individu, kelompok dan kelembagaan, baik formal maupun informal. Para pendamping bertindak sebagai penyedia dukungan bagi korban kekerasan seksual. Pendamping sering mengalami kesulitan karena korban merasa sulit untuk membuka diri karena trauma yang mereka alami. Strategi untuk berkomunikasi diperlukan, sehingga pendamping dapat memberikan dukungan dan bantuan dengan baik kepada korban. Penelitian ini ingin mengeksplorasi strategi komunikasi yang digunakan oleh pendamping dalam menangani dan membantu korban kekerasan seksual. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis deskriptif. Data dikumpulkan melalui wawancara mendalam. Informan dari penelitian ini adalah pendamping yang menangani korban kekerasan seksual. Informan kunci terdiri dari tiga orang, yaitu seorang polisi untuk perlindungan perempuan dan anak (PPA), psikolog yang menjadi korban kekerasan seksual, dan pendeta (relawan gereja). Hasil studi menunjukkan bahwa pendamping menerapkan strategi komunikasi dengan menerapkan prinsip empati, dukungan dan kesetaraan, sehingga para korban bersedia untuk membuka diri dan mendapatkan bantuan. Mereka menerapkan teknik hubungan baik dalam membangun hubungan, melatih keterampilan mendengarkan aktif, dan melakukan pengungkapan diri agar setara dengan korban, sehingga korban bisa lebih terbuka.